A Comparative Evaluation of ELISA, PCR, and Serum Agglutination Tests For Diagnosis of Brucella Using Human Serum - Khashayar Mohseni; Reza Mirnejad; Vahab Piranfar; Shiva Mirkalantari (Iranian Society of Pathology, 2017)
Background & Objective: Since the symptoms of Brucellosis are often atypical and nonspecific, using clinical signs alone to diagnose brucellosis is not advised; therefore, the diagnosis relies predominantly on laboratory testing. Currently, molecular, serological, and microbiological methods are used for diagnosis of this disease. In this study we examined ELISA, PCR and serum agglutination (SAT) methods on human patient serum samples. Methods:A total of 100 serum samples were collected from suspected patients. Fifty serum samples gave a positive result with the Wright test. The ELISA method was first employed on all samples for the detection of IgG and IgM antibodies against Brucella. Subsequently, the rapid PCR methodology was used to identify presence of Brucella genome in 500 µL of each serum sample. The B4/B5 primer pair was used for PCR‌ amplification. Results:Out of the 100 serum samples obtained from patients with suspected brucellosis, 50 samples tested positive by SAT and displayed high titers of 1/160. Of these 50 positive samples, 49 samples were positive as per the ELISA test whereas one sample tested negative. The PCR test was conducted on all 100 serum samples and results showed that the 45 serum samples that gave a positive agglutination test were also positive by PCR. Conclusions: Various laboratory methods have beenused or introduced for the detection of Brucella. Molecular methods such as PCR, a rapid and sensitive method for detection of bacteria, have also been reported. Based on the results of this study, we propose that the simultaneous use of serology and molecular techniques has the potential to overcome limitations of detection thereby enabling the selection of appropriate treatment for the patient.